Penegakan Hukum Peraturan Daerah Nomor 11 Tahun 2015 Tentang Penyelenggaraan Reklame di Kabupaten Kendal Oleh Satuan Poisi Pamong Praja - Putra, Diaz Angger Novarizhendy; Listyarini, Dyah; Megawati, Wenny (Wajah Hukum, 2024)
In the business world, advertising plays a crucial role in the success of a company's marketing of goods and services. Billboards, banners, and advertising banners on the streets have become common as effective tools for introducing products or services to the public. This research employs a qualitative method with a focus on advertising enforcement by the Regional Police Unit in Kendal Regency. This approach allows for a direct relationship between the researcher and the respondents. The results indicate that the enforcement of advertising laws in accordance with Regional Regulation Number 11 of 2015 has been implemented. Preventive law enforcement methods are utilized, such as verbal warnings to individuals who violate regulations by placing advertisements in unauthorized locations. Despite effective law enforcement, there are still issues with some individuals not fully complying with the regulations. Some prohibited advertisements mandated by the government remain in place, indicating suboptimal implementation of these regulations. In such cases, non-compliant advertisements can be dismantled in accordance with the rules established in the Regional Regulation of Kendal Regency.